2011
DOI: 10.1161/circulationaha.111.047498
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor Compared With Clopidogrel by Geographic Region in the Platelet Inhibition and Patient Outcomes (PLATO) Trial

Abstract: on behalf of the PLATO Investigators Background-In the Platelet Inhibition and Patient Outcomes (PLATO) trial, a prespecified subgroup analysis showed a significant interaction between treatment and region (Pϭ0.045), with less effect of ticagrelor in North America than in the rest of the world. Methods and Results-Reasons for the interaction were explored independently by 2 statistical groups. Systematic errors in trial conduct were investigated. Statistical approaches evaluated the likelihood of play of chanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
243
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 398 publications
(255 citation statements)
references
References 23 publications
3
243
1
5
Order By: Relevance
“…This was hypothesized to be the main reason for the impaired efficacy and higher bleeding rate noted in patients in North America compared with the rest of the world, and was confirmed using Cox proportional regression and landmark analyses after evaluating 36 potential factors that could account for the observed geographical variation. This work by Mahaffey et al formed the basis for the FDA black box warning on discharge aspirin dosing in patients receiving ticagrelor 3. Nevertheless, there is currently a paucity of data describing the real‐world practice patterns of discharge aspirin regimen in the United States, and our report represents one of the first and largest analyses on this topic.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This was hypothesized to be the main reason for the impaired efficacy and higher bleeding rate noted in patients in North America compared with the rest of the world, and was confirmed using Cox proportional regression and landmark analyses after evaluating 36 potential factors that could account for the observed geographical variation. This work by Mahaffey et al formed the basis for the FDA black box warning on discharge aspirin dosing in patients receiving ticagrelor 3. Nevertheless, there is currently a paucity of data describing the real‐world practice patterns of discharge aspirin regimen in the United States, and our report represents one of the first and largest analyses on this topic.…”
Section: Discussionmentioning
confidence: 87%
“…A subanalysis from PLATO identified a significant treatment–geographic region interaction ( P =0.045) and reported a reduced efficacy of ticagrelor versus clopidogrel in North American patients 3. A comprehensive systematic analysis independently identified differences in aspirin dosing as the likely reason for the observed interaction 4.…”
Section: Introductionmentioning
confidence: 99%
“…First, while propensity score adjustment has been reported to eliminate > 90% of the treatment bias in observational cohorts, observational studies are still subject to residual and unmeasured confounding bias 14. Second, although aspirin dose was not captured in this study, the data here may represent outcomes associated with use of high‐dose aspirin (≥300 mg day −1 ) as the PLATO study demonstrated reduced efficacy of ticagrelor with high‐dose aspirin 23, an interaction not seen with prasugrel in TRITON‐TIMI 38 24. Third, while implications of ticagrelor‐induced nonplatelet side effects (e.g., dyspnea, ventricular pauses) and of a twice‐daily dosing regimen on medication adherence and discontinuation are largely unknown, these factors may confer an increased risk for subsequent cardiac events, especially given the more rapid offset of the antiplatelet effect of ticagrelor.…”
Section: Discussionmentioning
confidence: 99%
“…28 No increased risk of overall or intracranial bleeding existed with ticagrelor therapy in those with a history of stroke or TIA. 30 Subsequent analysis of the trial, spurred by the finding of no benefit in the North American cohort of patients, revealed that the benefits of ticagrelor over clopidogrel for reduction in ischaemic events are observed only when the daily aspirin dose is ≤100 mg, 31 which is now reflected in a recommendation on package labelling. 32…”
Section: Ticagrelormentioning
confidence: 99%